Analysis of the Influence of Human Resources Management Practices and Knowledge Management on Employee Performance with Employee Development as a Mediating Variable at PT XYZ In Jakarta - Hanifah, Hanifah; Yohana F. Cahya Palupi Meilani (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of Human Resources Management Practices and Knowledge Management on Employee Performance with Employee Development as a mediating variable at PT XYZ in Jakarta. The method used is quantitative research with Partial Least Square - Structural Equation Modeling (PLS-SEM) technique. Data were collected from 50 respondents who are permanent employees of the company. The results of the study indicate that Human Resources Management Practices do not have a significant effect on Employee Development, while Knowledge Management has a positive and significant effect on Employee Development. Furthermore, Human Resources Management Practices and Knowledge Management have a significant effect on Employee Performance, while Employee Development does not have a significant effect on Employee Performance. Mediation analysis shows that Employee Development is not able to be a significant mediating variable in the relationship between Human Resources Management Practices and Knowledge Management on Employee Performance. This finding indicates that human resource management practices and knowledge management have an important role in improving employee performance, but employee development does not always have a direct impact on improving performance. Therefore, companies need to optimize employee development strategies to be more effective in improving individual performance.   Keywords: Human Resources Management Practices, Knowledge Management